Family Capital for Business Resilience during the COVID-19 Crisis - Novita, Dian; Handriana, Tanti; Purnamasari, Wulan (European Journal of Family Business, 2025)
Family firms are often regarded as more resilient than non-family firms, yet little is known about how this resilience develops from family-specific resources, particularly in emerging economies. This study explores how family capital—human, social, and financial—helped Indonesian family firms navigate the challenges of the COVID-19 crisis. Drawing on a multiple case study of four family-owned SMEs, we adopted an abductive approach, combining in-depth interviews with secondary data to build theory from context. The findings show that human capital, such as intergenerational learning and role flexibility, enabled firms to adapt quickly, while social capital, built on trust and long-term relationships, supported continuity and renewal. Financial capital acted as a buffer but was less central than expected. Overall, resilience emerged not from individual resources but from the interaction of these capitals. The study contributes to theory by reframing resilience as a relational capability embedded in family and cultural context, rather than as a static firm attribute. For practice and policy, the study highlights the importance of strengthening family members’ commitment, intergenerational skills, and relational networks, while deploying financial capital strategically to ensure continuity.